PENDAMPINGAN PENGEMBANGAN USAHA WARUNG MAKAN DI PAKIS TIRTOSARI UNTUK MENINGKATKAN PENJUALAN - Irawati, Desrina Yusi; Purba, Lasman Parulian; Canariesa, Armadeo Ruben; Massa, Paschal Nicollas Dominggo (ABIDUMASY, 2025)
Small and medium enterprises (SMEs) commonly found in communities include food and beverage stalls, which contribute significantly to local economic development and job creation. Warkop DC, a coffee shop located in Surabaya, faces several operational challenges including malfunctioning cooking equipment and supporting tools, outdated and uninformative business signage, poor business management practices, and limited understanding of online marketing strategies and business hygiene standards. To address these issues, the community service team implemented comprehensive solutions including business management training, online marketing education, hygiene practice workshops, equipment replacement, and business signage redesign. The community service methodology began with problem identification through discussions, followed by field observations at Warkop DC. Based on field assessment, feasible intervention strategies were selected and implemented according to mutual agreements, followed by continuous monitoring and evaluation. The community service program was successfully executed with positive outcomes. The partner experienced significant improvements including new operational equipment, more informative business signage, enhanced marketing through WhatsApp and online platform partnerships, establishment of standardized menu listings, and implementation of daily sales recording systems.